Réponses

2014-04-17T22:11:32+02:00
Bonsoir,

Factoriser l expression: 
B = 4x² - 4x + 1 - (2x - 1)(5x + 3)
    = (2x - 1)² - (2x - 1)(5x + 3)
    = (2x - 1)(2x - 1) - (2x - 1)(5x + 3)
    = (2x - 1) [(2x - 1) - (5x + 3)]
    = (2x - 1) (2x - 1 - 5x - 3)
    = (2x - 1) (-3x - 4)
2014-04-17T23:04:36+02:00
Factoriser l'expression
B = 4x² - 4x + 1 - (2x - 1) (5x + 3)
B = (2x - 1)² - (2x - 1) (5x + 3)
B = (2x - 1) (2x - 1) - (2x - 1) (5x + 3)
B = (2x - 1) ((2x - 1) - (5x + 3))
B = (2x - 1) (2x - 1 - 5x - 3)
B = (2x - 1) (- 3x - 4)